1996
DOI: 10.1620/tjem.180.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complications between Endoscopic Sinus Surgery and Caldwell-Luc Operation.

Abstract: Endoscopic sinus surgery (ESS) was compared with Caldwell-Luc (C-L) operation based on blood loss during surgery, operation time, period of hospitalization and complications. Both blood loss and operation time were significantly reduced in ESS as compared with C-L operation. In addition, patients undergoing ESS resulted in discharges after surgery earlier than those undergoing C-L operation. Minor complication was seen in 4.8% of the ESS patients whereas no major complication was recognized. ESS is a relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 13 publications
1
30
0
3
Order By: Relevance
“…If a true informed consent was obtained explaining the risks, benefits and the outcomes of both treatment options, it is very difficult to understand how a consent for Caldwell-Luc could be obtained. The authors findings are definitely valid, but similar findings have been demonstrated more than a decade and half earlier [1,2] and this study is like ''reinventing the wheel'' at the expense of patients who did not receive the 'standard of care' even when that was available. The authors should have done a thorough review of literature before conducting a study when considerable morbidity is associated with one treatment option compared to the other.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…If a true informed consent was obtained explaining the risks, benefits and the outcomes of both treatment options, it is very difficult to understand how a consent for Caldwell-Luc could be obtained. The authors findings are definitely valid, but similar findings have been demonstrated more than a decade and half earlier [1,2] and this study is like ''reinventing the wheel'' at the expense of patients who did not receive the 'standard of care' even when that was available. The authors should have done a thorough review of literature before conducting a study when considerable morbidity is associated with one treatment option compared to the other.…”
supporting
confidence: 84%
“…As rightly noted by authors themselves Caldwell-Luc is fairly abandoned in the treatment of chronic sinusitis for various reasons including-(a) Increased incidence of complications when compared to endoscopic sinus surgeries [1], (b) decreased cure rates when compared to endoscopic sinus surgeries [2]. Endoscopic sinus surgery is more physiological because it adheres to the principles of mucosal clearance and hence mucosal preservation is emphasized.…”
mentioning
confidence: 99%
“…(15) In relation to the access, the opening of anterior wall, as practiced by the Caldwell Luc technique, contribute to more risk of complication postoperative as sensorial alterations, penetration of soft tissue inside of the sinus, creating sinusitis and other pathologies like surgical cysts. (17,18) However, authors showed the absence of the relation of the opening of anterior wall, in this surgery, with complications. (19) More than that, showed through of sinuscopia the perfect harmony of the implant inside of maxillary sinus with normal mucosa around the fixations.…”
Section: Discussionmentioning
confidence: 87%
“…The time taken for the procedure is found to be more in Caldwell-Luc group when compared to FESS group. In a study conducted by Ikeda et al [14] it was found that the cooperation of patients was much better in the FESS group as compared to the Caldwell-Luc's surgery group. In our study anterior nasal packing with medicated ribbon gauze was done in only 12 patients of middle meatal antrosomy, while an antral pack brought out via the inferior meatal antrostomy opening was done in all patients of Caldwell-Luc.…”
Section: Discussionmentioning
confidence: 95%